Foveal configurations with disappearance of the foveal pit in eyes with macular pucker: Presumed role of Müller cells in the formation of foveal herniation. (June 2021) - Bringmann, Andreas; Unterlauft, Jan Darius; Barth, Thomas; Wiedemann, Renate; Rehak, Matus; Wiedemann, Peter
Abstract: Many eyes with macular pucker are characterized by a centripetal displacement of the inner foveal layers which may result in a disappearance of the foveal pit. In this retrospective case series of 90 eyes with macular pucker of 90 patients, we describe using spectral-domain optical coherence tomography different foveal configurations with ectopic inner foveal layers, document the relationship between posterior vitreous detachment (PVD) and idiopathic epiretinal membrane (ERM) formation and spontaneous and postoperative morphological alterations of the fovea, and propose an active role of Müller cells in the development of foveal herniation. We found that ERM were formed during or after partial perifoveal PVD, or after foveal deformations caused by tissue edema. The ERM-mediated centripetal displacement of the inner foveal layers and in various eyes anterior hyaloidal traction caused a disappearance of the foveal pit and an anterior stretching of the foveola with a thickening of the central outer nuclear layer (ONL). After the edges of the thickened inner layers of the foveal walls moved together, continuous centripetal displacement of the inner foveal layers generated a bulge of the fovea towards the vitreous (foveal herniation). Macular pseudoholes with a herniation of the inner foveal layers show that the outer layer of the protruding foveal walls is the outer plexiform layer (OPL). If the ERM covered the foveal walls and parafova, but not the foveola, the inner layers of the foveal walls were not fully centripetally displaced and the foveal pit was present. The visual acuity of eyes with ectopic inner foveal layers was inversely correlated with the thickness of the foveal center. Spontaneous morphological alterations after disappearance of the foveal pit may include the development of cystoid macular edema or additional thickening of the foveal tissue and foveal herniation. The foveal configuration with ectopic inner layers of the foveal walls and a thick central ONL persisted over longer postoperative time periods. The data show that the centripetal displacement of the inner foveal layers in eyes with macular pucker, which results in a disappearance of the foveal pit, may also generate foveal herniation which is suggested to be caused by contraction of Müller cell processes in the OPL. The centripetal displacement of the inner foveal layers and the formation of foveal herniation are suggested to reverse the foveal pit formation during development. Highlights: Macular pucker may involve centripetal displacement of the inner foveal layers. The displacement may also cause foveal herniation. The outer layer of the herniation is the outer plexiform layer. Contraction of Müller cell processes in this layer may form the herniation. The tissue displacement may reverse the developmental foveal pit formation.